Improving managerial competencies of middle managers at Vinh Phuc Power Company = Nâng cao năng lực quản lý của đội ngũ cán bộ cấp trung tại Công ty Điện lực Vĩnh Phúc - Nguyễn, Hà Thu (2020)
This research aims to achieve the following objectives: Identify the requirements of managerial competencies of middle managers at PC Vinh Phuc. Analyze current managerial competencies and identify the gap between required and current managerial competencies of middle managers at PC Vinh Phuc. Propose solutions and recommendations to improve managerial competencies of middle managers at PC Vinh Phuc.